STRATEGI KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DASAR DALAM MENGGERAKAN PARTISIPASI MASYARAKAT DI KOTA JAMBI - Yoga Pratama; Yantoro; Muhammad Sholeh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the transformational leadership strategies of elementary school principals in mobilizing community participation in three public elementary schools in Jambi City: SDN 64/IV, SDN 54/IV, and SDN 42/IV. A qualitative case study design was employed to explore the planning, implementation, and evaluation processes based on the four dimensions of transformational leadership proposed by Bass & Avolio: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. The findings show that in all three schools, principals successfully established strong partnerships with the community through vision-based planning, innovative and context-responsive program implementation, and participatory evaluation involving all stakeholders. These strategies enhanced community support in moral, material, and manpower forms, creating a more conducive and accountable school environment. The study concludes that transformational leadership effectively strengthens school– community collaboration and improves educational quality at the elementary level.